N-Lobe of TXNIP Is Critical in the Allosteric Regulation of NLRP3 via TXNIP Binding - Cheng, Fengyu; Wang, Nan (Frontiers in Aging Neuroscience, 2022)
Inflammasomes are cytoplasmic complexes that form in response to exogenous microbial invasions and endogenous damage signals. Among the known inflammasomes, the activation of the NACHT (NAIP, CIITA, HET-E, and TP1 domain), leucine-rich repeat, and pyrin domain containing protein 3 (NLRP3) inflammasome is also primarily related to neuroinflammation and nerve cell damage. Previous studies reported that under the stimulation of dangerous signals like reactive oxygen species (ROS), the overexpression and interaction of thioredoxin-interacting protein (TXNIP) with NLRP3 may trigger the inflammatory response through the ROS/TXNIP/NLRP3 signaling pathway. This inflammatory response is the pathophysiological basis of some neurological and neurodegenerative diseases. The activation of inflammasome and apoptosis caused by TXNIP are widespread in brain diseases. However, the comprehensive model of the TXNIP/NLRP3 interaction is still unclear. In this study, molecular docking experiments based on the existing crystal model of NLRP3 were performed to investigate the binding of TXNIP and NLRP3. Three in silico models of the TXNIP/NLRP3 complex were selected, and molecular dynamics simulations evaluated the binding stability of the possible interaction between the two proteins. The results revealed that the E690, E693, and D745 residues in NLRP3 and the K212 and R238 residues in TXNIP play a critical role in the TXNIP/NLRP3 interaction. N-terminal of TXNIP is essential in promoting the conformational changes of NLRP3, although it does not directly bind to NLRP3. Our findings reveal the possible binding mechanism between TXNIP and NLRP3 and the associated allosteric regulation of NLRP3. The constructed models may also be useful for inhibitor development targeting the TXNIP/NLRP3 interaction during inflammasome activation via the ROS/TXNIP/NLRP3 pathway.